The Application Of Technical Trading Rules: A Comparative Study Between Seven Equity Markets In Asia - Tan, Kelvin Kong Guan (2003)
The main objective of this study is to examine and compare the efficacy of employing simple technical trading rules against the buy-and -hold strategy in various Asian equity markets.